Duodenal Stenosis Caused by Helicobacter Pylori: Mimicker of Chronic Constipation - Taniguchi, Kazuto; Nakashima, Takema; Ichiyama, Yasunobu; Yamamoto, Hirokazu; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2018)
Although the most common causes of childhood chronic constipation are functional, a minority have an organic cause. We report an 11-year-old girl who was diagnosed as chronic constipation, but actually suffered from duodenal stenosis caused by Helicobacter pylori. An enhanced computed tomography was useful for investigation. Duodenal stenosis should be listed as a differential diagnosis for childhood chronic constipation.